Sifat Mekanika Bambu Petung Laminasi - Nor Intang Setyo H.; Iman Satyarno; Djoko Sulistyo; T.A. Prayitno (Jenderal Soedirman University, 2014)
Laminated bamboo is a kind of engineered structure to improve mechanical properties of bamboo. It is done in order to meet the need of building materials to the building structure. Laminated bamboo are constructed by gluing a slice bamboo, so it has its advantages can be made in any size and a more uniform mechanical properties of natural bamboo. Mechanical properties is required for structural analysis. Good modeling in structural analysis and numerical properties must be supported by valid mechanical properties. ASTM D143 explains the procedure in getting the mechanical properties of wood . This study refers to ASTM D143 to get laminated bamboo mechanical properties of the material are then arranged in a linear elastic lamina mulitilayer Orthotropic . Proficiency level parameter values for bamboo laminate is Young's Modulus ( E ) , EL = 11 840 MPa ; ER = 511.14 MPa ; ET = 814.39 MPa , Poisson ratio νLR = 0.179 ; νLT = 0.229 ; νRT = 0.231 , and Modulus Slide (G , MPa) GLR = 2.6112 ; GLT = 1.0435 ; GRT = 1.0435.